TEORI PEMBELAJARAN BAHASA DAN IMPLEMENTASI STRATEGI PEMBELAJARAN AKTIF - Hisyam Zaini (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2017)
Learning language theory and implementation of active learning strategy is expected to show one picture and motivation for the academic community by inviting the learner to actively do or perform any process of learning language based on the theory and strategy of active learning. This method is included in student-centered learning approach or student-centered learning. The author also wants to illustrate the mistaken implications of the implementation of learning strategies and change the paradigm, that language learning is not only a necessary cognitive factor but involves all elements of learning that include the cognitive, physical, mental and emotional aspects. In addition, in the process of language learning it is not enough to rely on one strategy and one method but to use diverse methods and strategies. Because, every method and strategy has their respective advantages